Moderate, excessive or heavy alcohol consumption: each is significantly associated with increased mortality in patients with chronic hepatitis C. Issue 7 (24th February 2013) - Younossi, Z. M.; Zheng, L.; Stepanova, M.; Venkatesan, C.; Mir, H. M.
Summary: Background: The impact of moderate alcohol consumption on long‐term outcomes of chronic hepatitis C (CH‐C) infected patients remains controversial. Aim: To assess the impact of moderate alcohol consumption on long‐term outcomes of CH‐C patients using population‐based data. Methods: Data were obtained from the Third National Health and Nutrition Examination Survey (NHANES III)‐mortality linked files. Alcohol consumption was estimated as grams/day. Multivariate Cox proportional hazards model was utilized to assess the effects of CH‐C and alcohol consumption on mortality (all causes, cardiovascular disease, and liver disease). Results: A total of 8985 participants were included as the study cohort. Of these, 218 had CH‐C. The follow‐up time was 162.95 months for CH‐C and 178.27 months for controls. CH‐C patients had increased risk for both overall mortality and liver‐related mortality. CH‐C patients with excessive alcohol consumption had even higher risks for overall mortality and liver‐related mortality. The risk of overall mortality associated with CH‐C increased with moderate alcohol consumption of 1–19 g/day and heavy alcohol consumption ≥30 g/day. Conclusion: Although chronic hepatitis C is associated with increased risks for overall and liver‐related mortality, these risks are even higher for patients consuming moderate and excessive amounts of alcohol.